2020
DOI: 10.7759/cureus.8072
|View full text |Cite
|
Sign up to set email alerts
|

Complete Resolution of a Large, Locally-advanced Cutaneous Squamous Cell Carcinoma with the Immune-modulating PD-1 Inhibitor Pembrolizumab

Abstract: Locally advanced cutaneous squamous cell carcinoma (cSCC) represents a challenge in treatment. Only very recently (February 2020) have guidelines been released regarding the management of unresectable, locally advanced cSCC. With the introduction of check point inhibitors during the last decade, anti-PD-1 antibodies represent a novel immunotherapeutic strategy in cancer. We present a case of an advanced cSCC not amenable to surgical resection, who experienced dramatic improvement following treatment with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Auch bei der Behandlung des lokal fortgeschrittenen cSCC scheint Pembrolizumab wirksam zu sein, wie die im Folgenden beschriebenen drei Fallberichte zeigen. Cristancho et al berichteten über einen Patienten mit inoperablem, lokal fortgeschrittenen cSCC, der Pembrolizumab 200 mg alle 3 Wochen erhielt und eine Vollremission CR erreichte, die mindestens 1 Jahr anhielt [80]. Unerwünschte Ereignisse wurden nicht beobachtet.…”
Section: Icb Bei Cscc: Wie Ist Die Derzeitige Evidenzlage?unclassified
“…Auch bei der Behandlung des lokal fortgeschrittenen cSCC scheint Pembrolizumab wirksam zu sein, wie die im Folgenden beschriebenen drei Fallberichte zeigen. Cristancho et al berichteten über einen Patienten mit inoperablem, lokal fortgeschrittenen cSCC, der Pembrolizumab 200 mg alle 3 Wochen erhielt und eine Vollremission CR erreichte, die mindestens 1 Jahr anhielt [80]. Unerwünschte Ereignisse wurden nicht beobachtet.…”
Section: Icb Bei Cscc: Wie Ist Die Derzeitige Evidenzlage?unclassified
“…Pembrolizumab also seems to be effective for the treatment of locally advanced cSCC as demonstrated by the following three case reports. Cristancho et al reported the case of a patient with unresectable, locally advanced cSCC who received pembrolizumab 200 mg Q3W and achieved a CR for at least 1 year [80]. No AEs were observed.…”
Section: Pembrolizumabmentioning
confidence: 99%
“…Cutaneous squamous cell carcinoma (CSCC) is a highly incident skin cancer that is often characterised by multifocal presentation and high rates of local recurrence after surgical excision. Advanced CSCCs include a small number of metastatic patients and more frequent cases of locally advanced disease unfit for both surgery and radiotherapy, which can only be treated by systemic therapy (2,3). Immunotherapy with antiprogrammed death ligand-1 (PD-1) agents is the gold standard in all current guidelines, and cemiplimab is the only recently approved anti-PD-1 antibody in Italy (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%